2006
DOI: 10.1007/s10661-006-1500-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Levels of Phthalate Ester Plasticizers in a Sewage Lagoon Effluent and a Receiving Stream

Abstract: In this study, samples from a sewage treatment lagoon and those from a receiving stream were analyzed for their phthalate esters content. Knowledge of the distribution of ubiquitous phthalate esters in the sewage lagoon and the receiving stream was necessary because of the reports of their subtle toxicity to aquatic biota and humans. Liquid-liquid extraction, Clean-up experiment and High Performance Liquid Chromatography (HPLC) were the methods employed for the quantitative determination of the Phthalates. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 26 publications
(16 reference statements)
3
20
0
Order By: Relevance
“…Fatoki et al (2010) studied phthalates in surface water and found concentrations which gave cause for concern with diethylhexyl phthalate (DEHP) posing the greatest risk (range 0.3-2.78 mg/L). Ogunfowokan et al (2006) assessed phthalates in a sewage lagoon and adjacent surface water. Both were assessed as being polluted by a range of phthalate compounds.…”
Section: Micro-organic Pollutantsmentioning
confidence: 99%
“…Fatoki et al (2010) studied phthalates in surface water and found concentrations which gave cause for concern with diethylhexyl phthalate (DEHP) posing the greatest risk (range 0.3-2.78 mg/L). Ogunfowokan et al (2006) assessed phthalates in a sewage lagoon and adjacent surface water. Both were assessed as being polluted by a range of phthalate compounds.…”
Section: Micro-organic Pollutantsmentioning
confidence: 99%
“…Several phthalate esters, dimethyl-(DMP), diethyl-(DEP), and di-n-butyl-(DBP) were found present at levels of 10 mg L -1 to 1472 mg L -1 in river water and 91 mg L -1 to 1219 mg L -1 in tap water from the cities' water treatment plants. Ogunfowokan et al (2006) investigated the levels and seasonal variations in the occurrence of PAEs in sewage oxidation pond at the Obafemi Awolowo University, Ile-Ife, Nigeria. The sewage lagoon and the receiving stream were grossly polluted as several phthalate ester plasticizers: dimethyl phthalate (DMP), diethyl phthalate (DEP), di-2-propyl heptyl phthalate (DPHP), dibutyl phthalate (DBP), diethyl hexyl phthalate (DEHP), di-octyl phthalate (DOP) and diisononyl phthalate (DINP) were found present at monthly mean levels of between 24.02 and 139.25 mg L -1 in the sewage treatment lagoon and 10.41 and 80.53 mg L -1 in the receiving stream.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The method of Ogunfowokan et al (2003Ogunfowokan et al ( , 2006 was used. The response factor of the standard OCPs was determined by analysing 1.0 μL of 1,000 ppm stock solution of the standard mixture containing the internal standard (I.S.)…”
Section: Determination Of Response Factormentioning
confidence: 99%